Place attachments to residents in Buring Rusunawa, Malang City - Rahmawati, Intan; Lestari, Sumi (Insight: Jurnal Ilmiah Psikologi, 2024)
Building facilities in flats is one of the main focuses in improving welfare. The Malang City Government is preparing itself to become a friendly city. One aspect that should be prepared is the suitability of housing which can increase life satisfaction and residential attachment among residents by considering health, comfort and ease of access. This research was carried out with the aim of knowing the dynamics of residential attachment among residents of Buring Flats, Malang City. Seeing this, the research design used was an exploratory sequential design. This design has two phases, namely the first phase will begin with qualitative techniques which are the main interpretation priority, then continued with quantitative in the second phase as confirmatory. The results of the research found that the residential attachment of the residents of Rusunawa Buring, Malang City is based on the existence of place dependence and place identity. The place dependence aspect can be seen from the availability of adequate facilities and services, as well as the utilization of these facilities. Meanwhile, the aspect of place identity is shown by the feeling of comfort they feel while occupying Rusunawa Buring. Keyword: Livability; place attachment; rusunawa.